2021
DOI: 10.1016/j.ijpe.2020.107929
|View full text |Cite
|
Sign up to set email alerts
|

The impact of online reviews in the presence of customer returns

Abstract: We develop a duopoly model to examine how online reviews influence the decisions of two competing online sellers who sell products of differentiated quality under different returns policies. We derive the competing sellers' optimal decisions on price and returns policy with and without online reviews, and we find that online reviews have greater impact on the high-quality seller than on the low-quality seller. If the salvage value of the product is relatively low, the seller has less opportunity to benefit fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Online reviews disclose additional information about products and services, and in this case, they can adjust current and potential customers' pre-purchase valuations of products and services in order to help them make better purchasing decisions. Therefore, there is a high potential of reducing customer retention and satisfaction [38,39].…”
Section: Online Reviews and Consumer Satisfactionmentioning
confidence: 99%
“…Online reviews disclose additional information about products and services, and in this case, they can adjust current and potential customers' pre-purchase valuations of products and services in order to help them make better purchasing decisions. Therefore, there is a high potential of reducing customer retention and satisfaction [38,39].…”
Section: Online Reviews and Consumer Satisfactionmentioning
confidence: 99%
“…However, more than that, in our study, we consider all the three possible return policies offered by a seller (including the partial-refund policy), and we highlight that more sellers are motivated to transfer their return policies to a partial-refund policy in the presence of social learning. Another key finding in Sun et al (2021) is that online reviews greatly impact the high-quality seller. Interestingly, in our study, a similar effect is observed on the monopolistic seller (with either a no-refund or partialrefund policy); that is, social learning benefits the seller when the product quality is high.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their study, Sun et al. (2021) highlight that around 90% of consumers read reviews before purchasing, and 88% trust these reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Luca and Zervas [34] analyzed Yelp reviews and combined the ratings of various shops to identify fraud and other behaviors. Sun et al [35] have studied how online reviews affect the return decisions of two competing online sellers selling products of different quality. Li et al [36] extracted six factors related to comments and two incentive factors for product sales from 28 studies focusing on online comments and sales to study how they affect product sales.…”
Section: Review Of Consumer Review Researchmentioning
confidence: 99%